Nidifica??o de Abelhas solit?rias (Hymenoptera: Apidae) em ninhos artificiais, Em Pomares de Acerola, na regi?o do Semi?rido baiano - Pina, Welber da Costa (2010)
Studies of the diversity and biology of bees in agricultural areas are still very scarce in Brazil. The present work examined the richness, abundance, annual activity, and biology of bee species that nest in trap-nests (=TN) and that have potential as pollinators of acerola orchards in the semiarid region near Feira of Santana, Bahia State, Brazil. Collections were made using trap-nests constructed from black cardboard (straws either 5 or 10 cm in length, 0.8 cm in diameter) that were inserted into cavities drilled length wise in wooden blocks. The TN were set in three orchards and inspected every month between October/2008 and September/ 2009. A total of 254 nests were obtained, with more nests in the orchards of family farms (n=134 e n= 94) than in experimental farms (n= 26). Centris analis, C. tarsata and Tetrapedia diversipes used the NT, with C. analis making the most nests (n= n=213). C. tarsata and T. diversipes nidified at low frequency (8.3% and 7.2% respectively) at all three sites. The three species utilized both TN tube lengths, although they nested with lower frequency in the smaller (n=65) than the larger tubes (n=189). The bees nested principally from December/2008 through April/2009. Natural enemies found in the nests included a species of Bombyliidae, Coelioxys sp, Mesocheira bicolor, Leucospis sp, and Coelioxoides sp. Our results indicate that C. analis is the most important local pollinator of acerola plants as measured by the high abundance of its nests, and suggests that this bee species offers significant potential for management for pollinating acerola orchards in the semiarid region of Bahia State.